PENGARUH CITRA DESTINASI DAN DAYA TARIK TERHADAP REVISIT INTENTION - Bagas Rahmadani Santoso; Agung Budiatmo; Naili Farida (Universitas Diponegoro, 2026)
Abstract: Tourist attractions are the hallmark of a region, especially Indonesia. The city of Semarang has a famous religious tourism icon, the Sam Poo Kong Temple. In the sustainability of tourist attractions, the action of revisit intention by visitors is needed to maintain the existence of these tourist attractions. Destination image and attractiveness are some of the factors that influence revisit intention. This study aims to determine the effect of destination image and attractiveness on revisit intention. This type of research is explanatory research with a quantitative approach using non-probability and purposive sampling techniques. Sampling was done by distributing questionnaires to visitors to the Sam Poo Kong Temple as many as 100 respondents. The data were analyzed using SPSS 25, which includes validity, reliability, correlation coefficient, coefficient of determination, simple linear regression analysis, multiple linear regression, t test, and F test. The results showed that destination image and attractiveness have a positive and significant effect on revisit intention. Both have a strong correlation with revisit intention. Attractiveness is proven to have a stronger influence in increasing revisit intention. The manager of Sam Poo Kong Temple Semarang is expected to pay more attention to aspects that can affect revisit intention.Abstrak: Tempat wisata menjadi keunggulan suatu daerah, terutama Indonesia. Kota Semarang memiliki ikon wisata religi yang terkenal, yaitu Klenteng Sam Poo Kong. Dalam keberlangsungan tempat wisata, diperlukan tindakan revisit intention oleh pengunjung untuk mempertahankan eksistensi tempat wisata tersebut. Citra destinasi dan daya tarik merupakan beberapa faktor yang mempengaruhi revisit intention. Penelitian ini bertujuan untuk mengetahui pengaruh citra destinasi dan daya tarik terhadap revisit intention. Tipe penelitian ini adalah explanatory research dengan pendekatan kuantitatif menggunakan teknik non-probability dan purposive sampling. Pengambilan sampel dilakukan dengan menyebarkan kuesioner kepada para pengunjung Klenteng Sam Poo Kong sebanyak 100 responden. Data dianalisis menggunakan SPSS 25, yang meliputi uji validitas, reliabilitas, koefisien korelasi, koefisien determinasi, analisis regresi linier sederhana, regresi linier berganda, uji t, dan uji F. Hasil penelitian menunjukkan bahwa citra destinasi dan daya tarik berpengaruh positif dan signifikan terhadap revisit intention. Keduanya memiliki korelasi kuat terhadap revisit intention. Daya tarik terbukti memiliki pengaruh yang lebih kuat dalam meningkatkan revisit intention. Pengelola Klenteng Sam Poo Kong Semarang diharapkan dapat memperhatikan lebih dalam aspek-aspek yang dapat mempengaruhi revisit intention.